COVID-19, Neuroimmunology and Neural Function - Heinbockel, Thomas; Weissert, Robert (IntechOpen, 2022)
The recent and ongoing COVID-19 pandemic has changed societies and research around the world. As such, this new book examines the latest developments in the field of neuroscience related to these changes. It includes six chapters in two sections: "COVID-19 Effects: Neurology, Neuroimmunology, Neurogenesis" and "Molecular and Cellular Neurochemistry." The first section includes chapters that address such topics as COVID's effect on adult neurogenesis, neurological manifestations of COVID-19, and COVID-19 and seizures. Chapters in the second section discuss peripheral biomarkers in multiple sclerosis, amino acids as neurotransmitters, advancements in RNA sequencing technologies, and more.